A Simple Method for Determining the HRV Parameters - Podaru, Alexandru Constantin; David, Valeriu (International Conference and Exposition on Electrical and Power Engineering (Online), 2020)
In this paper, we present a simple way to determine the heart rate variability (HRV) parameters. We designed a device which is capable of simultaneously recording three biological signals, namely the electrocardiographic signal (ECG), the photoplethysmographic signal (PPG) and a pulse signal acquired from the earlobe, graphically represented by the rectangular form. We recorded and processing these signals from 14 subjects. All data was recorded in the same way, namely with the participant sitting on a chair and by using the same sampling frequency. We determined the heart rate variability (HRV) parameters from the electrocardiographic signal, the pulse rate variability (PRV) parameters from the photoplethysmographic signals, and earlobe PRV from the pulse signal (ePRV). We calculated the Pearson coefficient in three ways, first between the HRV and the PRV parameters, second, using the HRV and the ePRV parameters and the last one using the PRV and the ePRV parameters. Both in case of the time-domain and frequency-domain parameters, the Pearson correlation coefficients were above 0.97, that means a strong link between HRV and ePRV/PRV.